PERBEDAAN PENGARUH PENYULUHAN MENGGUNAKAN MEDIA VIDEO DAN BONEKA TANGAN TERHADAP PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA SISWA SEKOLAH DASAR - Fastabiqul Hanif; Prasko Prasko (Jurnal Kesehatan Gigi, 2018)
TITLETHE DIFFERENCE OF COUNSELING WITH VIDEO MEDIA AND HAND PUPPETS TO IMPROVING KNOWLEDGE OF DENTAL AND ORAL HEALTH IN ELEMENTARY SCHOOL STUDENTSABSTRACT Knowledge less regarding oral hygiene is one cause of child neglect oral health problems. Knowledge of oral health in children of school groups deserve special attention because at this age children are undergoing the growth process of previous dental situation will influence the development of dental health in adulthood. Through training programs is expected to increase knowledge and raise awareness of the importance of maintaining oral health and able to participate actively in increasing efforts to nurture ourselves.Purpose of this study is to know the difference influence of illumination using video media and a hand puppet to the improvement of oral health.This study is a quasi experimental design with Two Group Design. Samples are students of SD Islam Diponegoro sampling purposive sampling technique. This study using univariate and bivariate data analysis with the Wilcoxon test and Mann-Whitney.This study shows that oral health education using video media and hand puppets influential in promoting oral health knowledge it can be seen from the pre-accession and post-test tet each with a value of p 0.05. But based on the statistical test no significant difference illumination using video media and hand puppets get the value of p = 0.465, which means p 0.005.Each media effective in improving knowledge but there is no significant difference between the method of video and hand puppets to increased knowledge of elementary school children about oral health.